Solve for y when 6y=9×3 Posted on October 23, 2021 By Dontcareanyonemo 3 Comments on Solve for y when 6y=9×3 Solve for y when 6y=9x3 Mathematics

square root of 36/6 = 2.449489743square root of 16/6 = 1.632993162square root of 6 = 2.449489743the answer is square root of 16/6 because the square root of 36/6 is the same answer as square root of 6 = 2.449489743Reply

x = -3y = -18step-by-step explanation:to solve by substitution, substitute one variable and solve for the other. then substitute again to find the remaining variable.x-1/3(3x-9) = -3 since y=3x-9 substittute y.x-1/3(3x-9)=-3x + x +3 = -32x+3=-32x+3-3= -3-32x=-6x=-3substitute again into y=3x-9y=3(-3)-9y=-9-9y=-18Reply

4.5Step-by-step explanation: since 6y=9x3, you can first multiply three and nine (which is 27). Then divide (27/6). Which equals to 4.5Reply

square root of 36/6 = 2.449489743

square root of 16/6 = 1.632993162

square root of 6 = 2.449489743

the answer is square root of 16/6 because the square root of 36/6 is the same answer as square root of 6 = 2.449489743

x = -3

y = -18

step-by-step explanation:

to solve by substitution, substitute one variable and solve for the other. then substitute again to find the remaining variable.

x-1/3(3x-9) = -3 since y=3x-9 substittute y.

x-1/3(3x-9)=-3

x + x +3 = -3

2x+3=-3

2x+3-3= -3-3

2x=-6

x=-3

substitute again into y=3x-9

y=3(-3)-9

y=-9-9

y=-18

4.5

Step-by-step explanation: since 6y=9x3, you can first multiply three and nine (which is 27). Then divide (27/6). Which equals to 4.5